ANALISIS PENGARUH CITRA MEREK, PROMOSI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN JASA TRANSPORTASI GOJEK (Studi Kasus Pada Pengguna Gojek di Bekasi Timur) - Mely Yani, (2022)
Gojek is an online transportation service popular in Indonesia, particularly in major cities such as East Bekasi. Because of its population growth and high mobility, Problems develop, one of which is traffic congestion, necessitating the use of quick, comfortabel, and safe transportation. This is a quantitative study to see how customer happiness for Gojek services in East Bekasi is affected by brand image, promotion, and service quality. Users of the Gojek in East Bekasi made up the research sample, which included 96 people. Non-probability sampling with a purposive sampling strategy was used for the sampling procedure. A questionnaire was used to collect data, and the SmartPLS 3.0 tool was used to analyze the results. According to the findings: (1) brand image has a positive and significant effect on customer satisfaction of 0.341, (2) promotion has a positive and significant effect on customer satisfaction of 0.539, and (3) service quality has a positive and significant effect on customer satisfaction of 0.357. While brand image, promotion, and service quality contributed to customer satisfaction with an Adjusted R square value of 0.623 while 37.7% caused other factor product quality, emotional factor and perceived convenience.